Novel modification of infrahyoid myocutaneous flap for the reconstruction of oral cavity defects. Issue 3 (April 2022) - Jafari, M.; Hekmati, R.; Karimi, E.; Heidari, F.; Alvandi, S.; Aghazadeh, K.; Firouzifar, M.; Erfanian, R.; Sohrabpour, S.
Abstract: This study was intended to describe the technique used and the results obtained with the modification of the infrahyoid flap (IHF) for the reconstruction of oral tongue defects following resection for advanced squamous cell carcinoma (SCC). Patients with oral tongue defects following ablation for T2 to T4a SCC had reconstructions using a modified infrahyoid flap. Demographic data, tumour characteristics, and the complications were evaluated for each patient. We observed no complications regarding the healing process of the donor site or success of the flap in 49 (of 55) patients. None of the flaps had massive oedema or venous congestion in the postoperative period. Six patients experienced flap-related complications of which five had partial skin paddle necrosis, but eventually their flaps recovered and re-epithelialised without any further intervention. However, total flap necrosis was seen in one patient in whom a pectoralis major flap was used for the defect reconstruction following revision surgery. History of previous radiotherapy to the neck (p = 0.003), tumour stage (p = 0.017), and metastasis to cervical lymph nodes (p = 0.004) were associated with higher prevalence of partial or total flap necrosis. The modified infrahyoid flap is a reliable, quick, and simple procedure with a reasonable cost that makes it a valuable option for the reconstruction of the oropharynx and oral cavity with minimal donor site morbidity and good outcomes. It seems the modified IHF is a valid surgical procedure that may be considered in selected patients undergoing reconstruction of oncological oral tongue defects with fewer complications.